2014
DOI: 10.4028/www.scientific.net/msf.778-780.631
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Nitridation Layer on 4H SiC (0001) Surface by Direct Plasma Nitridation

Abstract: A nitride layer was formed on a SiC surface by plasma nitridation using pure nitrogen as the reaction gas at the temperature from 800°C to 1400°C. The surface was characterized by XPS. The XPS measurement showed that an oxinitride layer was formed on the SiC surface by the plasma nitridation. The high process temperature seemed to be effective to activate the niridation reaction. A SiO2film was deposited on the nitridation layer to form SiO2/nitride/SiC structure. The interface state density of the SiO2/nitrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Shirasawa et al reported on the formation of an epitaxial silicon oxynitride SiON layer on a 6H-SiC (0001) surface, which offers great potential for device applications [6]. We have tried to form a nitride layer on the SiC surface by plasma nitridation [7]. Pure nitrogen was used as the reaction gas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shirasawa et al reported on the formation of an epitaxial silicon oxynitride SiON layer on a 6H-SiC (0001) surface, which offers great potential for device applications [6]. We have tried to form a nitride layer on the SiC surface by plasma nitridation [7]. Pure nitrogen was used as the reaction gas.…”
Section: Introductionmentioning
confidence: 99%
“…The thickness of the nitride layer was several nm and too small to measure the C-V characteristics. A SiO 2 layer was formed on the nitride layer by thermal chemical vapor deposition (CVD) method using tetraethoxysilane (TEOS) to obtain sufficient thickness for interface characterization by C-V method [7].…”
Section: Introductionmentioning
confidence: 99%